Uncomplicated Resistance Training and Health-Related Outcomes: Evidence for a Public Health Mandate - Phillips, Stuart M. (2010)
PHILLIPS, S.M. and R.A. WINETT. Uncomplicated Resistance Training and Health-Related Outcomes: Evidence for a Public Health Mandate. Curr. Sports Med. Rep., Vol. 9, No. 4, pp. 208–213, 2010. Compared to aerobic training (AT), resistance training (RT) has received far less attention as a prescription for general health. However, RT is as effective as AT in lowering risk for cardiovascular disease, diabetes, and other diseases. There is a clear ability of RT, in contrast to AT, to promote gains, maintenance, or slow loss of skeletal muscle mass/strength. Thus, as an antisarcopenic exercise treatment, RT is of greater benefit than AT; given the aging of our population, this is of primary importance. In our view, a substantial barrier to greater adoption of RT is the incorrectly perceived importance of variables such as external load, intensity, and volume, leading to complex, difficult-to-follow regimes. We propose a more feasible and easier-to-adhere-to paradigm for RT that could affect how RT is viewed and adopted as a prescription for public health.